The molecular basis of the chemosensitivity of metastatic cutaneous melanoma to chemotherapy. Issue 11 (5th October 2010) - Parker, Katharine A; Glaysher, Sharon; Polak, Marta; Gabriel, Francis G; Johnson, Penny; Knight, Louise A; Poole, Matthew; Narayanan, Ajit; Hurren, Jeremy; Cree, Ian A
Abstract : Background: Chemotherapy benefits relatively few patients with cutaneous melanoma. The assessment of tumour chemosensitivity by the ATP-based tumour chemosensitivity assay (ATP-TCA) has shown strong correlation with outcome in cutaneous melanoma, but requires fresh tissue and dedicated laboratory facilities. Aim: To examine whether the results of the ATP-TCA correlate with the expression of genes known to be involved in resistance to chemotherapy, based on the hypothesis that the molecular basis of chemosensitivity lies within known drug resistance mechanisms. Method: The chemosensitivity of 47 cutaneous melanomas was assessed using the ATP-TCA and correlated with quantitative expression of 93 resistance genes measured by quantitative reverse transcriptase PCR (qRT-PCR) in a Taqman Array after extraction of total RNA from formalin-fixed paraffin-embedded tissue. Results: Drugs susceptible to particular resistance mechanisms showed good correlation with genes linked to these mechanisms using signatures of up to 17 genes. Comparison of these signatures for DTIC, treosulfan and cisplatin showed several genes in common. HSP70, at least one human epidermal growth factor receptor, genes involved in apoptosis ( IAP2, PTEN ) and DNA repair ( ERCC1, XPA, XRCC1, XRCC6 ) were present for these agents, as well as genes involved in the regulation of proliferation ( Ki67, p21, p27). The combinations tested included genes represented in the single agent signatures. Conclusions: These data suggest that melanoma chemosensitivity is influenced by known resistance mechanisms, including susceptibility to apoptosis. Use of a candidate gene approach may increase understanding of the mechanisms underlying chemosensitivity to drugs active against melanoma and provide signatures with predictive value.